BUDAYA ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): ANALISIS KOMITMEN AFEKTIF GURU DI SEKOLAH DASAR NEGERI - Minkhaermidah; Tri Agustina M; Fuad Abdul Baqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Organizational effectiveness in public elementary schools is strongly influenced by teachers’ willingness to perform extra-role behaviors that support school goals. Organizational culture is considered a key factor in shaping such behaviors, particularly through teachers’ affective commitment. This study aims to analyze the relationship between organizational culture and Organizational Citizenship Behavior (OCB) by examining the mediating role of teachers’ affective commitment in public elementary schools. The study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to public elementary school teachers and analyzed using descriptive statistics and inferential analysis, including mediation testing. The results indicate that organizational culture has a positive and significant effect on affective commitment and OCB. Furthermore, affective commitment significantly influences OCB and partially mediates the relationship between organizational culture and OCB. These findings suggest that a positive organizational culture strengthens teachers’ emotional attachment to the school, which in turn encourages voluntary behaviors that contribute to school effectiveness. The study highlights the importance of strengthening organizational culture and affective commitment to enhance teachers’ organizational citizenship behavior in public elementary schools. Keywords: organizational culture, organizational citizenship behavior, affective commitment, teachers, public elementary schools